A comprehensive study on the livelihood implications of transitioning from cocoa to rubber plantation in Ghana - Busia, Joseph Oppong; Amankwah, kwadwo; Appiah, Patrick; Tham-Agyekum, Enoch Kwame; Bakang, John-Eudes Andivi (Indonesian Coffee and Cocoa Research Institute, 2024)
The study, conducted in Manso Amenfi, Western Region, Ghana, explored the livelihood implications of transitioning from cocoa to rubber plantations. Using a cross-sectional survey with 384 participants, data revealed a decline in cocoa production levels. The socioeconomic factors that influence farmers’ land use shift behaviour were age, household size, being a household head, farm size, educational level, access extension and labour availability. The knowledge factor that was ranked first as influencing farmers shift behaviour was high price of rubber while the behavioural factor was the farmers’ personal belief that rubber plantation will do well than cocoa. The farmers agreed that rubber plantation has effect on their livelihood. The study recommends interventions to make cocoa cultivation more profitable, addressing concerns like low prices, pests, diseases, and soil fertility, emphasizing the need for support from agricultural extension officers, the Ghana Cocoa Board, and the government.